Synthesis of Cellulose–Polylactic Acid Microcapsule as a Delivery Agent of Rifampicin - Suripto Dwi Yuwono; Ridho Nahrowi; Andi Setiawan; Ni Luh Gede Ratna Juliasih; Irza Sukmana; Wasinton Simanjuntak; Sutopo Hadi (Science and Technology Indonesia, 2022)
In medicinal field, delivery agent is a very important substance to improve the efficiency of drug used by improving the stability and preventing the degradation of drug during the medical treatment. Due to these important roles of the drug delivery agent, the search of effective agent is continuously in progress. In this respect, this current research was carried out to synthesize cellulose–polylactic acid (cellulose-PLA), as a potential delivery agent of rifampicin for the curing of tuberculosis. Cellulose was isolated from cassava bagasse, while PLA was obtained from commercial supplier. The two raw materials were used to synthesize cellulose–PLA in 3.5% HCl as solvent under magnetic stirring. The product obtained was then characterized by Fourier-Transform Infrared spectroscopy (FTIR), Particle-Size Analysis (PSA), and Scanning Electron Microscopy (SEM). The FT-IR result showed the presence of hydroxy (3446 to 3429 cm−1) and carbonyl (1757 to 1759 cm−1), confirming the formation new bond between cellulose and PLA. The PSA characterization displays a particle-sizes of PLA are in the range of 960–92780 nm, while cellulose–PLA are in the range of 100–17730 nm demonstrating that cellulose-PLA combined to form more compact structures. The results of SEM analysis indicate the distinct feature of cellulose-PLA, and combination of the features in the cellulose and PLA image. The results of the dissolution test carried out two different concentrations of rifampicin revealed that the optimum dissolution (8.42%) was achieved with cellulose–PLA of 0.3%, dissolution time of 12 h, and pH of 7.4.